Herbal medicine and acupuncture for mild cognitive impairment: a retrospective study of 2,242 for older adults in Republic of Korea - Suh, Hyo-Weon; Lim, Jae Hwan; Suh, Jin-woo; Park, Chan; Park, Yong-Sin; Chung, Sun-Yong (Frontiers in Neurology, 2025)
IntroductionDementia prevalence increases with age, underscoring the importance of early intervention for mild cognitive impairment (MCI). However, standard treatment recommendations for MCI remain lacking. Herbal medicine and acupuncture have been proposed as potential alternatives. This study evaluated the feasibility and effectiveness of these interventions in patients with MCI.MethodsWe conducted a retrospective cohort study using data from a public health promotion program for community-dwelling older adults in Korea who received acupuncture, with or without herbal medicine, between 2021 and 2023. Feasibility was assessed by completion of acupuncture sessions and follow-up. Exact propensity score matching was performed using age, sex, comorbidities, depression scores, and health-related behaviors to compare herbal medicine add-on versus acupuncture only groups. Clinical outcomes included cognitive function [the Cognitive Impairment Screening Test (CIST) and the Montreal Cognitive Assessment (MoCA)] and depression [Geriatric Depression Scale–Short Form (GDS-SF)].ResultsOf 5,525 participants, 4,623 received acupuncture with or without herbal medicine. Feasibility was high, with 86.4% completing planned acupuncture sessions; among these, 93.8% also received herbal medicine. Loss-to-follow-up rate was lower in the herbal medicine add-on (4.1%) than in the acupuncture-only (12.1%). After matching, 2,242 participants were included (2,044 herbal medicine add-on and 198 acupuncture-only). Both groups showed significant improvements in CIST, MoCA, and GDS-SF scores, with the herbal medicine add-on group demonstrating significantly greater cognitive improvement in the CIST (coefficient: 0.58; 95% CI, 0.10–1.08).ConclusionHerbal medicine combined with acupuncture appeared feasible and potentially effective for managing MCI, supporting its practicality in community settings. However, its therapeutic benefits need to be further validated through rigorously designed randomized controlled trials. Long-term studies are warranted to confirm these findings and clarify their role in dementia prevention.